Evaluation of Lotions of Botanical-Based Repellents Against Aedes aegypti (Diptera: Culicidae). Issue 2 (4th November 2020) - Qualls, Whitney A; Xue, Rui-De; Farooq, Muhammad; Peper, Steven T; Aryaprema, Vindhya; Blore, Kai; Weaver, Richard; Autry, Dena; Talbalaghi, Asghar; Kenar, James; Cermak, Steven C; Zhu, Junwei J
Abstract: Thirteen botanical product repellent compounds such as 2-undecanone, capric, lauric, coconut fatty acids (and their methyl ester derivatives), and catnip oil were formulated in either Coppertone or Aroma Land lotions and evaluated against laboratory-reared Aedes aegypti L. (Diptera: Culicidae) mosquitoes. These formulations contained 7–15 wt/wt of the botanical repellent as the major active ingredient either pure or as mixtures. USDA standard repellent test cages were used to determine the complete protection time (CPT) of the different formulated repellents. Two of the evaluated formulations, a 7% capric acid in Coppertone (CPT 2.7 ± 0.6 h) and 7% coconut fatty acids containing carrylic acid, capric acid, and lauric acid in Coppertone (CPT 2.3 ± 2.0 h), provided strong repellency against mosquitoes up to 3 h, which was equivalent to the ( N, N -diethyl- m -toluamide) DEET control (CPT 2.7 ± 0.6 h). This work suggests future potential for these botanical product-based repellents as alternatives to commercial DEET-containing products.